2008
DOI: 10.1016/j.jneuroim.2008.04.021
|View full text |Cite
|
Sign up to set email alerts
|

Bi-directional heterologous desensitization between the major HIV-1 co-receptor CXCR4 and the κ-opioid receptor

Abstract: We previously characterized multiple interactions between chemokine and opioid G-protein coupled receptors (GPCR), and we found both µ and δ-opioid receptors cross-desensitize CCR1, CCR2, CCR5, but not CXCR4. Here we report that the κ-opioid receptor (KOR) is able to cross-desensitize CXCR4, and this phenomenon is bi-directional. Chemotactic responses by KOR activation are diminished with prior activation of CXCR4. Additionally, calcium mobilization assays show these cross-desensitization processes occur withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
50
0
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 65 publications
(54 reference statements)
3
50
0
4
Order By: Relevance
“…2E-G). Other studies also reported cross-desensitization of the CXCL12/CXCR4-mediated chemotaxis of T lymphocytes by the chemokine receptor CCR5 (11), the k-opioid receptor (25), and the TCR complex (26). Consistent with our data, the results of these investigations showed a partial ] i was measured in FURA 2-AM-loaded Th1 cells by spectrophotometry.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…2E-G). Other studies also reported cross-desensitization of the CXCL12/CXCR4-mediated chemotaxis of T lymphocytes by the chemokine receptor CCR5 (11), the k-opioid receptor (25), and the TCR complex (26). Consistent with our data, the results of these investigations showed a partial ] i was measured in FURA 2-AM-loaded Th1 cells by spectrophotometry.…”
Section: Discussionsupporting
confidence: 92%
“…The observed reduction in CXCR4 surface expression upon CXCL9 stimulation may also be the result of a modulation in transporting CXCR4 from intercellular vesicles to plasma membrane and was not necessarily a result of receptor desensitization and internalization. Nevertheless, the observed magnitude of CXCR4 downregulation is similar to comparable investigations reporting CXCR4 cross-desensitization by stimulation with ligands for CCR5, the k-opioid, or the TCR (25,26,34). To test whether CXCL12-dependent activation of prominent signaling molecules is modulated by CXCL9, we measured phosphorylation of Akt (Ser473), which was shown to be affected by a heterologous desensitization of CXCR4 upon CCR5 receptor stimulation (10,11).…”
Section: Discussionsupporting
confidence: 75%
“…Several studies have shown that opiates, including morphine (the major metabolite of heroin, which easily reaches the brain), alter CXCR4 function in immune and neural cells (24)(25)(26). Recently, our group has shown that morphine (and selective μ-opioid receptor [MOR] agonists, such as DAMGO) specifically impairs CXCL12/CXCR4 signaling in neurons, both in vitro and in vivo, by increasing protein levels of ferritin heavy chain (FHC), a recently described CXCR4 regulator (25,(27)(28)(29).…”
Section: Introductionmentioning
confidence: 99%
“…Both CB2 and CXCR4 are G i/o -coupled receptors. Potential mechanisms by which activation of CB2 receptors might inhibit the signaling of CXCR4 are suggested by the interactions of opiates with CXCR4 and include CXCR4 internalization, the formation of inactive heterodimers, and expression of proteins that inhibit chemokine receptor function (Finley et al, 2008;Pello et al, 2008;Sengupta et al, 2009).…”
mentioning
confidence: 99%